2015
DOI: 10.5567/ecology-ik.2015.13.23
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Enzyme Expression in a Macrophytic Treated Crude Oil Soil Habitat: Implication for Enhanced Phytoremediation Potential Using Transgenic Botanicals

Abstract: Background: Several studies have demonstrated the success of phytoremediation and its advantages over conventional physical and biochemical (even engineered transgenics) methods, resulting in its use on many contaminated sites. A direct method for enhancing the effectiveness of phytoremediation is to over express the genes in transgenic plants that are involved in metabolism, uptake and/or transport of specific pollutants. Objective: A screen-house ecological study was carried out to evaluate the remediation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…This could suggest a longer period of phytoremediation duration as earlier affirmed by Wang et al [36]. The greater performance of P. pterocarpum in enhancing hydraulic conductivity could be attributed to its potency in improving the soil porosity, texture, structure, particle density and reduction in bulk density, organic matter and THC content as reported in this research and the influence of botanical explants (enzyme) in the rhizosphere soil [50].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…This could suggest a longer period of phytoremediation duration as earlier affirmed by Wang et al [36]. The greater performance of P. pterocarpum in enhancing hydraulic conductivity could be attributed to its potency in improving the soil porosity, texture, structure, particle density and reduction in bulk density, organic matter and THC content as reported in this research and the influence of botanical explants (enzyme) in the rhizosphere soil [50].…”
Section: Resultssupporting
confidence: 75%
“…This corroborate Merki et al [48], Wang et al [49], Wang et al [36], Udom and Nuga [37] who have earlier reported a similar higher degradation and removal of petroleum hydrocarbon in vegetated soils than non vegetated bulk soil. The performance of P. pterocarpum could be attributed to its extensive root system, which could be represented in a positive correlation (r = 0.40; P=0.05) between the plant root and THC content of the soil and also in the activities of the detoxifying enzyme of the plant [50]. The root system of plant species are capable of penetration into impermeable soil, thus it become desirable for phytoremediation to have plants that grows with dense ramified fibrous root system deep down [51].…”
Section: Resultsmentioning
confidence: 99%